Return of the sorceress - Waggoner, Tim.; Rams, Vinod (Renton, WA : Wizards of the Coast, 2004)
The fourth title in an all-new Dragonlance series for young readers. Return of the Sorceress continues a new series of Dragonlance adventures written specifically for readers ages 10 and up. Sized to fit the young reader market, the series features a new group of young companions who band together for friendship and excitement during the golden age of the Dragonlance world. Author Tim Waggoner, who wrote the first title in this series, Temple of the Dragonslayer, has written frequently for young readers, and his novels and short stories have been nominated for numerous writing awards.
"Mirror stone."
Accelerated Reader AR
Keywords: Krynn (Imaginary place) -- Juvenile fiction